Reproductive and staygreen trait response of maize hybrids, improved openpollinated varieties, and farmers local varieties to terminal drought stress - Kamara, A.Y.; Menkir, A.; Badu-Apraku, Baffour; Ibikunle, O. (2003)
In the dry savanna of West and Central Africa, where unpredictable rainfall and recurrent drought are major constraints to maize production, the development of tropical maize genotypes with high and sable yields under drought is very important since access to drought-tolerant genotypes may be the only affordable alternative to many small-scale farmers. Consequently, IITA began screening maize genotypes under controlled conditions for tolerance to drought stress in 1998. Some drought tolerant genotypes have been identified and are undergoing further improvement. Field studies were carried out in 2001 and 2002 to determine the response of drought adaptive traits (flowering, stay-green and leaf area index) in six of the maize genotypes already evaluated under drought. These traits are useful in the improvement of maize genotypes for tolerance to drought since they have been found to improve the efficiency of selection for drought tolerance. The traits were planted in two separate but adjacent blocks representing two irrigation treatment (water-deficit and well-watered conditions). Water was applied by sprinkler irrigation to the blocks of the two trails every 7 days from planting to the end of the fourth week (28 days). Thereafter, the irrigation was terminated for the block with the water -deficit treatments. Hybrids and open pollinated varieties (OPV) showed the same grain yeild potential under irrigated conditions and performed better than the land races. Under induced moisture stress, the trend was the same but the OPV performed better than the hybrieds. Differences in grain yield under drought were strongly associated with reduced anthesis silking interval (ASI) and high leaf area index (LAI). Leaf death scores did not significantly correlate with grain yield but were highly correlated with LAI, indicating the importance of green leaf area for the maintenance of high grain yield under drought.